PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA DALAM SISTEM PERADILAN PIDANA ANAK (STUDI PUTUSAN NOMOR 2/PID.SUS-ANAK/2024/PN BPP) - Aida, Nur; Muslim, Ikhwanul; Sunariyo, Sunariyo (Jurnal Ilmiah Dinamika Hukum, 2025)
This research discusses the legal protection for children involved in drug abuse as transaction intermediaries. The main focus of this research is the application of rehabilitation in the juvenile criminal justice system, emphasizing the importance of recovery rather than punishment. This research utilizes the normative literature method and approaches legislation, cases, and conceptual. The decision was analyzed to determine the form of legal protection that can be given to children with drug abuse cases. The findings indicate that Law No. 11/2012 on the Juvenile Criminal Justice System emphasizes that children must receive protection from the investigation stage until the legal process takes place. However, in practice, judges still often impose prison sentences without considering aspects of social and medical rehabilitation. This research recommends that the justice system prioritize rehabilitation to ensure optimal recovery and social reintegration of children, which is in line with child protection theory and restorative justice theory. Keywords: Legal Protection, Children, Rehabilitation